Anti-Corruption Education in an Indonesian Government-Affiliated Academy: Graduates’ Perspectives on How Education Influenced their Behaviour in their Workplace - Nungki Awalya Ramdhani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Preventing corruption through education programs is considered beneficial to the current efforts to curb corruption in Indonesian government sector. The present study explores how an anti-corruption educational program in a government-affiliated academy can influence the academy’s graduates. Three graduates of the academy who have worked in the government sector participated in this research. This qualitative study conducted semi-structured interviews with each participant. Kirkpatrick’s four-level evaluation model was used as the theoretical basis for assessing the impact of learning result in behavioural changing in the workplace. The findings of this study provide evidence that the anti-corruption program is positively linked to positive behaviour promoting anti-corruption values in the workplace. The participants perceived that the program helped them to develop a better understanding of the existing rules and regulations pertaining to corruption, changed their paradigm about corruption, and equipped them with the ability to be agents of change within the organisation.Pencegahan korupsi melalui program pendidikan dipandang bermanfaat dalam upaya pemberantasan korupsi di sektor pemerintahan Indonesia saat ini. Penelitian ini mengeksplorasi bagaimana program pendidikan antikorupsi di sekolah kedinasan yang berafiliasi dengan pemerintah dapat mempengaruhi alumni instansi pendidikan tersebut. Tiga alumni yang bekerja di sektor pemerintahan berpartisipasi dalam penelitian ini. Penelitian kualitatif ini melakukan wawancara semi terstruktur kepada masing-masing partisipan. Model evaluasi empat tingkat Kirkpatrick digunakan sebagai landasan teori untuk menilai dampak hasil pembelajaran terhadap perubahan perilaku di tempat kerja. Hasil penelitian ini menunjukkan bahwa program antikorupsi berhubungan positif dengan perilaku positif yang mempromosikan nilai-nilai antikorupsi di tempat kerja. Para peserta menyatakan bahwa program tersebut membantu mereka mengembangkan pemahaman yang lebih baik mengenai peraturan dan perundang-undangan terkait anti korupsi, memperluas paradigma mereka tentang korupsi, dan membekali mereka dengan kemampuan untuk menjadi agen perubahan dalam organisasi.